Modelagem Matemática e Análise de Modelos Matemáticos na Educação Matemática - Soares, Débora da Silva; Javaroni, Sueli Liberatti [UNESP] (My University, 2012)
In this paper we present two studies, the first one completed and the second one in development, which are based in teaching approaches that propose the qualitative study of mathematical models as a strategy for the teaching and learning of mathematical concepts. These teaching approaches focus on subjects from Higher Education such as Introduction to Ordinary Differential Equations and Topics of Differential and Integral Calculus. We denominate this common aspect of the teaching approaches as Model Analysis and in a preliminary level we relate it with Mathematical Modeling. Furthermore, we discuss some questions related with the choice of the theme and the role of Digital Technologies when Model Analysis is applied.

Neste artigo apresentamos duas pesquisas, a primeira delas concluída e a segunda em fase de desenvolvimento, que têm como base abordagens pedagógicas que propõem o estudo qualitativo de modelos matemáticos como uma estratégia de ensino e aprendizagem de conceitos matemáticos. Estas propostas estão direcionadas para disciplinas do Ensino Superior, como Introdução às Equações Diferenciais Ordinárias e Tópicos de Cálculo Diferencial e Integral de funções de uma variável real. Denominamos este aspecto em comum das abordagens pedagógicas como Análise de Modelos e procuramos relacioná-lo, ainda que em um nível preliminar, com a Modelagem Matemática. Além disso, discutimos questões acerca da escolha do tema escolhido e sobre o papel das Tecnologias Digitais quando Análise de Modelos é aplicada.
Keywords: Geometrical approach; Ordinary differential equations; Digital technologies; Abordagem geométrica; Equações diferenciais ordinárias; Tecnologias digitais